View on Ancient Philosophy and its Legacy: between Soviet and Chinese Marxism - Vitalii Turenko (International Society of Philosophy and Cosmology, 2022)
The article reveals the peculiarities of the interpretation of ancient philosophy in two directions of Marxism - Soviet and Chinese. The author emphasizes the common and distinctive features of understanding philosophy in Soviet and Chinese philosophy. Proved that Soviet Marxism saw the most important stage in the formation and development of philosophy as a phenomenon of world culture in ancient philosophy. At the same time, Soviet thinkers tried to find the key points of ancient philosophy that would correlate with the main Marxist ideas. Also, based on the principles of Marxism, Soviet historians of philosophy analyzed and identified both common and commonplace moments in ancient Greek and ancient Chinese philosophy. It was revealed that Soviet and Chinese thinkers, first of all, try to find those moments in ancient philosophy that are directly or indirectly connected with Marxist philosophy - its principles, values, and ideas. At the same time, as part of the study of ancient philosophy, a whole corpus of translations from ancient Greek was carried out, although ancient Roman thinkers were less in demand for Soviet Marxism. Whereas, within the framework of Chinese Marxism, there is still a lot to be done in the context of the philosophical translation of the ancient heritage. However, argued thesis that to some extent, Chinese Marxism developed more intensively in the context of research of ancient philosophy. After all, in addition to purely ideological works devoted to the understanding of ancient philosophy, research began to develop actively in terms of comparative philosophy and classical reception studies.